Congenital dermatofibrosarcoma protuberans. - Ingravallo, G.; Lastilla, G.; Minervini, C.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
Dermatofibrosarcoma protuberans is a lowmalignity neoplasia with high rate of relapses. It has characteristic cytogenic alterations. The tumor is rare in children (3, 4), although already described at birth (1). Some diagnostic problems may arise in children, because its clinical features can be reminiscent of scleroatrophy or keloid (2). The histological examination shows a proliferation of fibrohistiocytic, CD34+, spindle cells with a storiform pattern of distribution, infiltrating the dermis and the connective septa of the subcutaneous fat tissue. The surgical removal should be generous due to the infiltrating tendency of the tumor. However, in children, especially in some sites, it is not always possible to maintain a large margin of resection.